Classification of European oak–hornbeam forests and related vegetation types. Issue 1 (9th March 2023) - Novák, Pavel; Willner, Wolfgang; Biurrun, Idoia; Gholizadeh, Hamid; Heinken, Thilo; Jandt, Ute; Kollár, Jozef; Kozhevnikova, Maria; Naqinezhad, Alireza; Onyshchenko, Viktor; Pielech, Remigiusz; Rašomavičius, Valerijus; et al.
Abstract: Aims: Oak–hornbeam forests and related vegetation types (phytosociological order Carpinetalia betuli ) are widespread in temperate western Eurasia. However, their national classification systems are poorly compatible, and a broad‐scale classification based on numerical analyses is lacking. Therefore, we aimed to establish a unified formalized classification system based on a large data set of vegetation plots covering the entire range of these forests. Location: Europe, Anatolia, Caucasus and northern Iran. Methods: We compiled a data set of 15, 817 vegetation plots from the European Vegetation Archive and the Hyrcanian Forest Vegetation Database, using the formal definition of the EUNIS habitat type T1E Carpinus and Quercus mesic deciduous forest. We classified the data set using TWINSPAN. Biogeographically and ecologically similar plot clusters were merged into oak–hornbeam forest types, which were interpreted as alliances. We also developed expert systems for automatically classifying vegetation at the alliance level for both the EuroVegChecklist (EVC) system and the revised classification. In addition, we calculated ordinations to show the major gradients in the species composition of the data set. Results: We present a revised classification system of the order Carpinetalia betuli with nine alliances, including basic descriptions of their species composition, distribution, ecology and syntaxonomy. The analyses largely supported the biogeographic concept of classification, analogous to EVC. Compared to EVC, we recognized an additional alliance Physospermo verticillati‐Quercion cerridis (southern Italy) but found no support for the alliances Astrantio‐Carpinion, Erythronio‐Carpinion and Scillo‐Quercion . The greatest difference in species composition was found between the southern and northern‐northeastern Carpinetalia types. Expert systems for the revised classification system ( 89% of plots classified) and the EVC system ( 72%) are also included. Conclusions: We provide the first comprehensive overview of alliances of the order Carpinetalia betuli across its whole distribution range. The associated expert systems allow consistent application of the classification of these forests in nature conservation, habitat monitoring, and biodiversity and ecological research. Abstract : We provide the first formal classification for oak–hornbeam forests and related vegetation types (phytosociological order Carpinetalia betuli ) across Europe and adjacent areas. It includes both traditional and revised classifications of this vegetation. Furthermore, we developed expert systems for vegetation‐plot assignment to vegetation types, which can be applied in research and biodiversity conservation, monitoring and management.